2020
DOI: 10.1111/birt.12483
|View full text |Cite
|
Sign up to set email alerts
|

Variation of intrapartum care and cesarean rates among practitioners attending births of low‐risk, nulliparous women

Abstract: Background: Variation in hospital cesarean birth rates across the United States is likely because of differences in practitioner practice patterns. Yet, few studies conducted in the last twenty years have examined the relationships between practitioner characteristics and the use of intrapartum interventions and cesarean birth. The objective of this study was to examine associations among practitioner characteristics and the use of amniotomy, epidural, oxytocin augmentation, and cesarean birth in low-risk wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Our descriptive study could not provide a reason for this finding, but future studies might explore possible nonclinical influences on rural cesarean births, including differing practitioner attitudes, 40 hospital culture, 39,41,42 use of birth professionals such as doulas, 43 or the impact of using delivery practitioners associated with lower cesarean rates such as midwives or family physicians. [44][45][46] This study has several limitations. We explored deliveries from a single payment source (ie, Medicaid), which may have incompletely characterized maternity services statewide, although a recently published study of a single private health plan noted similar results.…”
Section: Discussionmentioning
confidence: 96%
“…Our descriptive study could not provide a reason for this finding, but future studies might explore possible nonclinical influences on rural cesarean births, including differing practitioner attitudes, 40 hospital culture, 39,41,42 use of birth professionals such as doulas, 43 or the impact of using delivery practitioners associated with lower cesarean rates such as midwives or family physicians. [44][45][46] This study has several limitations. We explored deliveries from a single payment source (ie, Medicaid), which may have incompletely characterized maternity services statewide, although a recently published study of a single private health plan noted similar results.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the CS rate of NTSV pregnancies is de ned as an important quality indicator of obstetric care 7,8 . NTSV CS rates vary widely throughout the world and among medical institutions, and physicians and nursing care providers have indicated that clinical practice patterns in labor and delivery units affect the number of CSs performed 9,10 . Various intrapartum care methods for reducing the rate of NTSV CS births have been proposed, and they mainly focus on labor management and fetal heart rate interpretation for care providers 6,7,11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…This is appropriate for hospital discharge data because ICD coding does not provide a way to accurately identify number of prior births. Although midwives do not perform cesarean surgery, care provided by midwives during pregnancy and labor is associated with lower rates of cesarean birth 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…Although midwives do not perform cesarean surgery, care provided by midwives during pregnancy and labor is associated with lower rates of cesarean birth. 15,16 Preterm birth was measured as any birth less than 37 completed weeks' gestation based on the ICD-10-CM codes for gestational age (Z3A). Records missing a gestational age ICD-10-CM code were excluded from analysis of preterm birth.…”
Section: Variables and Measurementmentioning
confidence: 99%